2017
DOI: 10.1111/exd.13397
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin and lymecycline treatments modify the skin microbiota in acne

Abstract: Oral retinoids and tetracyclines have a major role in acne treatment. Here, we report for the first time the effect of isotretinoin and lymecycline therapy on the skin microbiota in cheek, back and armpit swab samples of acne vulgaris patients using 16S ribosomal RNA (16S rRNA) gene amplicon sequencing. Propionibacterium acnes was the most common in sebaceous areas of healthy and untreated acne skin and more abundant in back than cheek samples. Five taxa, including a Streptococcus taxon, differed significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 44 publications
7
57
2
3
Order By: Relevance
“…Acne improved and Propionibacterium abundance decreased after various treatments, together with an increase of microbial diversity in the two controlled studies. Moreover, a positive correlation between Propionibacterium abundance and acne severity grade was found 54, 55.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Acne improved and Propionibacterium abundance decreased after various treatments, together with an increase of microbial diversity in the two controlled studies. Moreover, a positive correlation between Propionibacterium abundance and acne severity grade was found 54, 55.…”
Section: Resultsmentioning
confidence: 81%
“…Moreover, acne improved and Propionibacterium decreased after treatment, while the microbial diversity increased 54, 55. Taking into account that a clear pathophysiological role of P. acnes exists and antimicrobial interventions are effective in AV 72, 73, the adoption of the skin microbiome as biomarker in acne drug development programmes is, although still in its infancy, suggested by our review (Table 2).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Culture‐independent technologies have revealed close relationships between the skin microbiome and chronic inflammatory dermatoses, such as atopic dermatitis, psoriasis and acne vulgaris (acne) . 16S rRNA gene sequencing showed that the skin microbiome is closely correlated with acne, and the dominant bacterial communities on the skin of acne patients were Cutibacterium , Staphylococcus , Corynebacterium , Streptococcus and Micrococcus …”
Section: Introductionmentioning
confidence: 99%